Komunitas Herpetofauna dan Potensinya bagi Sektor Ekowisata pada Kawasan Ketenger-Baturraden di Selatan Kaki Gunung Slamet, Jawa Tengah - Awal Riyanto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
I expressed the distribution, broad habitat association, and ecotourism potential of herpetofauna based on four habitat types on Ketenger-Baturraden,MountSlamet,Central Java. The data was gathered by opportunistic searching. Sorensen index was used to determine similarity between communities; and cluster analysis was used to determine the habitat utilization. As the results, 35 species were recorded, comprising 16 frogs, 11 lizards and 8 snakes. The species richness was decreased from natural forest to habitat types that open and having homogenous vegetation. The herpetofauna communities between natural forest and limited production forest had the highest similarity (50%). The natural forest is important habitat and should be conserved. Based on habitat types, there were nine groups of herpetofauna. The ecotourism potential of herpetofaunal richness on Ketenger-Baturraden is not yet exploited.